Chemical engineering : visions of the world - Darton, Richard; Wood, D. G.; Prince, R. G. H. (Elsevier, 2003)
This book presents six visionary essays on the past, present and future of the chemical and process industries, together with a critical commentary. Our world is changing fast and the visions explore the implications for business and academic institutions, and for the professionals working in them. The visions were written and brought together for the 6th World Congress of Chemical Engineering in Melbourne, Australia in September 2001. Identifies trends in the chemicals business environment and their consequences Discusses a wide variety of views about business and technology Describes the impact of newly developing technologies.